Rethinking the Rat Trilogy: Detachment, Commitment and Haruki Murakami’s Politics of Subjectivity - A. K. Byron (New Voices in Japanese Studies, 2017)
The career of novelist Haruki Murakami has conventionally been divided into two periods: detachment and commitment. Murakami’s transition to commitment, in the sense of a social engagement with a defined political sensibility, is generally seen to begin with the novel The Wind-Up Bird Chronicle [1995]. However, the so-called Rat Trilogy (Hear the Wind Sing [1979], Pinball, 1973 [1980] and A Wild Sheep Chase [1982]) sees Murakami address the concept of shutaisei—the question of individual agency and subjectivity at the centre of Japan’s student activist movement in the late 1960s. Examining the trilogy’s central characters through the lens of shutaisei, I argue that a commitment to political and historical awareness can already be found in Murakami’s early works.